Enter the water, come to the table : baptism and Lord's supper in scripture's story of new creation - Hicks, John Mark. (Abilene, Texas : Abilene Christian University Press, 2014)
A rich resource for renewing the practice of the sacraments in a way that encourages faithful discipleship in a hostile cultural environment. As evangelicals and other Christians continue the renewal and deepening of their practice of the sacraments, Enter the Water, Come to the Table provides an accessible study. It explores the meaning and practice of baptism and the Lord's supper through the lens of the biblical story's movement from creation to new creation. Rooting this sacramental journey in the Exodus of Israel, this book shows how Jesus inaugurates a new Exodus from old creation into new creation. Jesus' own baptism and table fellowship with his disciples embody the kingdom of God as new creation realities. And in light of Jesus' death and resurrection, baptism and the Lord's supper not only promise a future but they mediate a transforming experience of new life now.
Print version record.
Master record variable field(s) change: 630, 650
Keywords: Bible -- Introductions; Creation -- Biblical teaching; Baptism -- Biblical teaching; Lord's Supper -- Biblical teaching; RELIGION -- Christian Theology -- Soteriology; Electronic books